Modelos discretos para an?lise de ocorr?ncia de erros em redes sem fio - Marcondes, Guilherme Augusto Barucke (2005)
Abstract: In most wireless communication channels, the incidence of errors in digital system tends to grouped shape to occur (in bursts). Such behavior reflects the characteristic of the channel memory, where the occurrence of an error is statistically dependent on the occurrence of errors in bits above. Several discrete models were presented in the literature to characterize the channels with memory. This paper presents some of these models, their characteristics and expressions for error statistics calculation (distribution of probabilities of: g-bit size gaps, b bits and m bits size bursts wrong in n bits transmitted). The parameters of the models were adjusted to allow for the characterization of these statistics in a channel with Rayleigh fading nonselective frequency in three different scenarios.